Analysis of the Relationship Between Digital Transformation Influenced by Technology, Artificial Intelligence Diagnosis, Legal Basis and Challenges to Health Services in Hospitals - Hilmy, Mohamad Reza; Putranto, Rahmat Dwi; Mahadewi, Erlina Puspitaloka; Setiawan, Ichwan; Shameela, Alika (Syntax Literate, 2026)
The rapid adoption of digital technologies and artificial intelligence (AI) is transforming hospital healthcare services, offering opportunities to improve diagnostic accuracy, operational efficiency, and patient-centered care. Previous studies indicate that AI-powered diagnostic tools, cloud computing, electronic health records, and IoT systems significantly enhance clinical decision-making and resource management. However, legal, ethical, and operational challenges including patient data privacy, liability ambiguity, staff skill gaps, interoperability issues, and high implementation costs pose significant barriers to effective adoption. This study aims to investigate the relationship between digital transformation driven by emerging technologies, AI-assisted diagnostics, legal frameworks, and operational challenges in hospital services. A systematic literature review (SLR) was conducted, analyzing peer-reviewed articles published between 2021 and 2025 from major databases including PubMed, Scopus, ScienceDirect, and Google Scholar. Key themes were extracted and synthesized across five dimensions: technology and infrastructure, AI implementation, legal and regulatory considerations, operational challenges, and healthcare outcomes. Findings reveal that while digital transformation and AI adoption enhance hospital efficiency and diagnostic precision, their success depends on coordinated attention to regulatory compliance, staff training, system integration, and organizational readiness. Hospitals must adopt multidimensional strategies to balance technological innovation with ethical, legal, and operational considerations for sustainable healthcare delivery.